2020
DOI: 10.1002/lsm.23341
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Ablative 1927 nm Fractional Thulium Fiber Laser: New, Promising Treatment Modality for Riehl's Melanosis

Abstract: Background and Objectives: The treatment of Riehl's melanosis, also known as pigmented contact dermatitis, is highly challenging. Intense pulsed light (IPL) and 1064 nm Q-switched Nd:Yag (QS-Nd:YAG) laser are reported to have some efficacy. However, no single effective treatment has yet been identified. In this study, we demonstrated the efficacy and safety of the non-ablative 1927 nm fractional thulium fiber laser (TFL, LASEMD™; Lutronic Corp., Goyang, Korea) for patients with Riehl's melanosis. Study Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Compared with other hyperpigmented disorders such as melasma, Riehls’ melanosis is more complicated and requires more time to treat [ 20 ]. Several regimens have been attempted with diverse outcomes in small population studies or case reports [ 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. However, there are no standard treatment guidelines established yet.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other hyperpigmented disorders such as melasma, Riehls’ melanosis is more complicated and requires more time to treat [ 20 ]. Several regimens have been attempted with diverse outcomes in small population studies or case reports [ 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. However, there are no standard treatment guidelines established yet.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical response was measured based on a quartile grading scale (Grade 1, <25%, minimal to no improvement; Grade 2, 26%-50%, moderate improvement; Grade 3, 51%-75%, marked improvement and Grade 4, >75%, near-total improvement). 5 To assess the severity of dermal pigmentation objectively, the dermal pigmentation area and severity index (DPASI) was used for the evaluation. 8 Patients were queried regarding their overall satisfaction levels, with response options ranging from 'very satisfied' to 'unsatisfied', with 'slightly satisfied' as a midpoint.…”
Section: Treatment Outcome Evaluationmentioning
confidence: 99%
“…2,3 Histopathological findings of studies of Riehl's melanosis show evidence of current or resolving interface dermatitis with pigment incontinence, indicating that the greyish pigmentation is due to dermal melanophages. 1,4,5 Later studies found by dermoscopic and…”
mentioning
confidence: 99%
“…The laser can probably target epidermal cells, reverse the disruption of the dermoepidermal junction (basement membrane), and induce neocollagenosis and elastinogenesis in the upper dermis. 36 Kim et al 37 considered that TFL could be a viable and promising therapy option for Riehl’s melanosis and has recently been attempted in their study, given that histopathologically RM and postinflammatory hyperpigmentation are similar. All nine patients were treated with more than three to seven sessions of TFL at the energy between 10 and 20 mJ.…”
Section: Laser Therapymentioning
confidence: 99%
“… Mi Yeon Cho, 2019 32 Wavelength and fluence: mid-plused 1064 nm with 3.5–5 J/cm2, spot size: 5 mm, 3 to 12 sessions at initially four-week intervals 21 76.1% of patients obtained moderate to much improvement through standardized photographs, the melasma area and severity index scores and skin biopsy Tolerable itching in one case and disappeared within few days, prolonged erythema and resolved within 2 weeks Lack of control group Takanori Iwayama, 2020 12 Wavelength and fluence: 755 nm with 0.25–0.71J/cm2, pulse-width: 750 ps, seven sessions at monthly intervals 1 Substantial improvement observed in clinical appearance and histopathology findings None Small simple size. Su Min Kim, 2021 37 TFL at the energy between 10 and 20 mJ, three to seven sessions at monthly intervals 9 Dermal pigmentation area and severity index score decreased from 9.55 to 5.25, the skin histology in one patient revealed a marked decrease in melanosomes in the epidermis and superficial dermis Transient erythema and swelling The shallow penetration of TFL cannot reach the deeper skin layer …”
Section: Laser Therapymentioning
confidence: 99%